2014
DOI: 10.1007/s12011-014-9973-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Dietary Chromium on Tissue Mineral Contents in Rats Fed Diets with Fiber

Abstract: This study evaluated the effects of diets with fiber (cellulose and/or pectin) supplemented with chromium(III) on homeostasis of selected minerals in femurs, thigh muscles, livers, and kidneys of rats. For 6 weeks, male rats were fed experimental diets: a fiber-free diet (FF), a diet containing 5 % cellulose (CEL), 5 % pectin (PEC), or 2.5 % cellulose and 2.5 % pectin (CEL + PEC). These diets had 2.53 or 0.164 mg Cr/kg diet. The tissue levels of Ca, Mg, Zn, Fe, and Cr were determined by using atomic absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Previous studies have reported that Cr supplementation can increase the Cr content of tissues, although the results varied [26, 27]. In our study, the Cr contents of breast meat and blood were very significantly increased with the inorganic and CEBS supplemented.…”
Section: Discussionsupporting
confidence: 41%
“…Previous studies have reported that Cr supplementation can increase the Cr content of tissues, although the results varied [26, 27]. In our study, the Cr contents of breast meat and blood were very significantly increased with the inorganic and CEBS supplemented.…”
Section: Discussionsupporting
confidence: 41%
“…SEBS, due to the effects of B. subtilis and Se, exerted a more robust effect. Previous studies have reported that Se supplementation can increase Se tissue content, although the results varied [58]. In our study, the Se contents in the plasma and liver increased signi cantly in the IS and SEBS groups, which indicated that the dietary supplement containing Se exerted a signi cant in uence on the Se level; this is in accordance with previous reports [37,57].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that Cr supplementation can increase the Cr content of tissues, although the results are varied (37)(38)(39)(40) . In our study, the Cr contents of the heart, liver, spleen, kidney and skeletal muscles were significantly increased with the addition of Cr in the inorganic form and as CEBS.…”
Section: Discussionmentioning
confidence: 99%